PROJECT TRACKING SYSTEM FOR SOFTWARE ENGINEERING LABORATORY (SE LAB) COURSE - Chow, Huey Meng (Universiti Malaysia Sarawak, (UNIMAS), 2020)
The purpose of Project Tracking System for Software Engineering Laboratory (SE Lab) Course is to provide an online platform that is available to track the progress of SE Lab Course project, to have a discussion with the clients of the projects and to enable evaluation of the project. In order to complete this system, the opinions of the post SE Lab students, clients and majorly the instructor are taken. Through this system, students, clients and instructor should be able to track and update progress anytime and anywhere compared to the existing system. This development of this system is using the Agile Feature Driven Development (FDD) method in collaboration with Tay Ya Sing for the Team Software Process (TSPi) Tools for building the complete system by pair programming. The expected outcome of this system will be operating the developed system throughout the SE Lab course in the Faculty of Computer Science and Information Technology.